Analysis of the Impact of Road Infrastructure Quality in Tegal City on User Satisfaction in Road Transportation: A Qualitative Study in Urban Areas - Nurjanah, Ajeng Devina (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Road infrastructure plays a crucial role in the efficiency and safety of transportation systems, particularly in urban areas where traffic demand is high. In Tegal City, the quality of road infrastructure directly affects user satisfaction with road transportation. Understanding this relationship is essential for urban planners and policymakers to enhance the transportation experience for residents.This study aims to explore the impact of road infrastructure quality on user satisfaction among road transportation users in Tegal City. By utilizing qualitative methods, the research seeks to gather in-depth insights into users' perceptions and experiences regarding the current state of road infrastructure.A qualitative approach was employed, involving semi-structured interviews with a diverse group of road users, including commuters, drivers, and public transport users. The interviews were conducted in various urban locations throughout Tegal City to capture a comprehensive understanding of user experiences. The data were analyzed thematically to identify key factors influencing user satisfaction. Based on survey results from 100 respondents, the majority rated the quality of road infrastructure in Tegal City with an average of 3.03, indicating a moderate level of satisfaction. Some respondents noted that there were still potholes and less than optimal maintenance. The level of satisfaction with road maintenance scored an average of 3.37, indicating that efforts had been made, but had not fully met residents' expectations. The condition of road signs was rated quite good with an average of 3.47, although some respondents mentioned the need for improvements to safety facilities such as guardrails and road markings. Most respondents also stated that road quality affected their travel experience, with an average score of 3.42. However, there are still shortcomings, especially regarding drainage systems and pedestrian facilities. In addition, a score of 3.25 for road suitability for vehicles and pedestrians indicates the need for a balance of infrastructure for both users.To improve the quality and satisfaction with road infrastructure, the government is advised to increase the road maintenance budget, including repairing potholes and rejuvenating damaged road surfaces. Drainage systems need to be improved to avoid puddles that can damage roads, especially during the rainy season. In addition, improved safety facilities and road signs, such as adequate night lighting, will support road user safety. Pedestal infrastructure. The insights gained from this research can inform local policymakers and urban planners in prioritizing infrastructure improvements that enhance user experiences. By addressing the identified issues, Tegal City can improve overall transportation satisfaction and contribute to a more efficient urban mobility system.